2013
DOI: 10.1111/scs.12078
|View full text |Cite
|
Sign up to set email alerts
|

At the mercy of others – for better or worse

Abstract: Many elderly people spend their remaining days in nursing homes and are thus affected by issues pertaining to a good life in a nursing home. The Norwegian study presented in this article aimed to gain greater knowledge and understanding of the significant factors associated with a good life in a nursing home. Qualitative in-depth interviews with six nursing home residents aged 80 to 96 years were conducted to collect data. The aim of the analysis was to identify typical aspects related to a good life in a nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…They proved their ability to act when decision‐making in matters of everyday life were based on life memories, having a variety of routines, and being able to do spontaneous or planned activities. Earlier findings show that having something to look forward to influences experiences in the present .…”
Section: Discussionmentioning
confidence: 82%
“…They proved their ability to act when decision‐making in matters of everyday life were based on life memories, having a variety of routines, and being able to do spontaneous or planned activities. Earlier findings show that having something to look forward to influences experiences in the present .…”
Section: Discussionmentioning
confidence: 82%
“…The residents want both physical and psychosocial care; being able to receive help when needed was important. 29 Unfortunately, lack of resources in terms of too few staff was crucial because there was too little time for social contact. In Norwegian primary healthcare, inadequate attention, the need for social contact, and physical activity or self-determination were ethical challenges experienced most frequently by healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…(quotation in Walker & Paliadelis, 2016, p. E8) However, in some studies, participants said it was inappropriate for staff and residents to be friends, and that staff should act like professionals (Bangerter et al, 2016). Residents also commented that they felt safe with staff who displayed professionalism and competence, communicated clearly, and were able to promptly recognize and respond to their needs (Bangerter et al, 2016;Dybvik et al, 2014;Palacios-Ceña et al, 2013;Rodríguez-Martín et al, 2013;van Hoof et al, 2016): "[staff should] be knowledgeable about the job . .…”
Section: Staff Attitudementioning
confidence: 99%
“…Poor attitude was associated with staff who avoided taking responsibility for residents' needs (Dybvik et al, 2014;Harrison & Frampton, 2017), treated residents like children (Donnelly & MacEntee, 2016), or lacked enthusiasm for their work (Donnelly & MacEntee, 2016). A resident in one study suggested staff are more likely to neglect residents with dementia or other disabilities that impede self-advocacy (Kang et al, 2020).…”
Section: Staff Attitudementioning
confidence: 99%